Utilisasi Animasi Bergerak Berbasis Artificial Intelligence (AI) Sketch Metademolab Sebagai Pengembangan Kreativitas dan Imajinasi Peserta Didik SDN 1 Sukorejo Nganjuk - Latifatul Jannah; Fernadiksa Rastra Putra Pratama (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
AI technology, which is currently widely used, can be used as a medium to foster students' enthusiasm for drawing and creativity. One that can be used is AI technology in the form of moving or giving motion effects to drawings made by students. In addition to developing students' imagination and creativity, this research activity can also improve teachers' abilities to become good and innovative teachers. Current problems are declining student interest in creating works, and a lack of teacher training regarding the use of technology in learning. The research conducted was by guiding children to draw illustrations of characters or something based on their imagination. Next, students were directed to upload the results of the drawings on the Sketch Demolab page and then students viewed them. The resulting image became a moving animation. The research was conducted to obtain data on student enthusiasm in creating works. The results showed that the use of Artificial Intelligence (AI) Technology Sketch Metademolab in effective moving animation activities can increase students' creativity and imagination. This was obtained from the results of questionnaires and interviews conducted with students at SDN Sukorejo 1. The results showed that students responded positively to this activity, with an average percentage of "YES" answers above 90%. This reflects that a learning approach based on creative practices such as drawing and animation is able to create a fun and meaningful learning experience. In addition, the use of AI technology in learning has been proven to have a positive impact in supporting the learning process of students, especially in honing critical thinking skills, imaginative, and adaptive to the development of the times. In addition, the use of AI technology in learning also provides an opportunity for students to better understand how technology can be applied in the world of art and creativity.